Self-reported memory and executive function in adult non-clinical hoarders. Issue 2 (4th March 2023) - Heffernan, Tom; Hamilton, Colin; Neave, Nick
Abstract: Hoarding is the excessive acquisition of, and failure to discard of, large numbers of items, leading to personal distress. Impairments on memory and executive functions have been systematically associated with hoarding behavior, predominantly focusing upon clinical (mainly middle-aged-elderly) patients with hoarding and/or PTSD. We were interested in hoarding-related memory and executive problems in younger non-clinical hoarders or non-hoarders, based on their Saving Inventory-Revised scores. In total, 113 young adults (aged 18–35 years) were assigned to either a hoarder group ( N  = 40) or non-hoarder group ( N  = 73) determined by their scores on the Saving Inventory-Revised (SI-R). Working memory (WM) and inhibition control (IC) were measured using the Adult Executive Functioning Inventory (ADEXI) and the Dysexecutive Questionnaire Revised ( DEX-R) measured general executive function (EF). The Hospital Anxiety and Depression Scale measured anxiety and depression. After controlling for gender and anxiety, the analysis revealed that the hoarders reported significantly more problems than the non-hoarders on both the IC and general EF. There was no significant between-group difference on the WM sub-scale ADEXI. Self-reported deficits in IC and EF are associated with hoarding behavior. The IC deficits cold explain hoarders' inability to resist urges to buy, and general EF deficits suggest other domains are involved.